2014
DOI: 10.1186/1472-6890-14-25
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine phosphorylase expression is associated with time to progression in patients with metastatic colorectal cancer

Abstract: Background5-Fluorouracil (5-FU) is the cornerstone of chemotherapeutic treatment for patients with colorectal cancer. The enzyme thymidine phosphorylase (TP) catalyzes the conversion of 5-FU to its active metabolite, 5-fluoro-2’-deoxyuridine. TP is expressed in tumour epithelial cells and stromal cells, particularly in tumour-associated macrophages. These macrophages may affect sensitivity to chemotherapy. Previously, we identified TP as a predictive factor in microdissected tumour samples of patients with adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
0
15
1
Order By: Relevance
“…However, five of these 20 studies did not offer eligible data and it was no possible to obtain exact survival information from these five articles. After completing the selection process, data from a total of 15 studies ( 4 , 5 , 24 29 , 35 41 ) involving 1225 patients ( Fig. 1 ) were systematically analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, five of these 20 studies did not offer eligible data and it was no possible to obtain exact survival information from these five articles. After completing the selection process, data from a total of 15 studies ( 4 , 5 , 24 29 , 35 41 ) involving 1225 patients ( Fig. 1 ) were systematically analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 15 studies, 9 ( 4 , 24 , 25 , 27 , 36 39 , 41 ) were conducted in Asia and seven were from Japan. A total of 10 ( 4 , 5 , 25 , 26 , 28 , 35 , 37 39 , 41 ) were retrospective studies, one ( 29 ) was a prospective study and the other four ( 24 , 27 , 35 , 40 ) were not stated. Although the chemotherapy regimen varied in all 15 articles, they all used 5-FU-based drugs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low TP expression, measured in one study by reverse transcriptase polymerase chain reaction (RT-PCR) and in another by immunohistochemistry (IHC) and tissue microarrays, correlated with improved treatment outcomes, in terms of overall survival (OS), in patients with mCRC treated with adjuvant 5-FU [Soong et al 2008;Salonga et al 2000]. A more recent study analyzed tumor tissue from mCRC by RT-PCR and found longer time to progression with high TP expression [Lindskog et al 2014]. Further well-designed trials are needed to establish a definitive link between TP expression and resistance to FP therapy.…”
Section: -Fumentioning
confidence: 99%
“…Gene expression analysis using quantitative real-time reversetranscription PCR (RT-qPCR) has been shown to be a promising tool to study molecular markers related with cell malignancy, chemoresistance and response to treatment [25][26][27][28][29] besides being a fast, sensitive, reproducible and specific method to analyze gene expression [30]. The normalization of this method is an important step to control the experimental errors introduced during the process, such as variability of RNA, variability of extraction protocols, RNA purity, inefficiency of reverse transcription, inaccurate quantification of RNA sample and errors of pipetting [31,32].…”
Section: Introductionmentioning
confidence: 99%